2008
DOI: 10.1080/19401490802021012
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring and modelling of manually-controlled Venetian blinds in private offices: a pilot study

Abstract: This study presents results from a window blind usage survey and field study that was conducted in California, USA during a period spanning from the vernal equinox to the winter solstice. A total of 113 office building occupants participated in the survey. Twenty-five occupants participated in the field study. In this study, 83 measurements of physical environmental conditions were cross-linked with participants' window blind controlling preferences. A total of 13 predictive window blind control bivariate and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 22 publications
(29 reference statements)
0
37
0
Order By: Relevance
“…In the literature, the variables considered in the monitoring and assessment of the occupants' control patterns are, typically: workplane (daylight) illuminance (Hunt 1979); average window luminance (Sutter, Dumortier et al 2006); maximum window luminance and background luminance (Inkarojrit 2008); DGI (Lee and Selkowitz 1995); DGP (Wienold and Christoffersen 2006); vertical transmitted direct solar radiation (Inoue, Kawase et al 1988); vertical incident global solar radiation (Foster and Oreszczyn 2001); and, duration of occupation/absence (Pigg, Eilers et al 1996;Mahdavi and Proglhof 2009). In the present study, it was decided that all parameters would be monitored so as to later assess to what extent the observed behaviour agrees with the behaviour suggested by each model.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature, the variables considered in the monitoring and assessment of the occupants' control patterns are, typically: workplane (daylight) illuminance (Hunt 1979); average window luminance (Sutter, Dumortier et al 2006); maximum window luminance and background luminance (Inkarojrit 2008); DGI (Lee and Selkowitz 1995); DGP (Wienold and Christoffersen 2006); vertical transmitted direct solar radiation (Inoue, Kawase et al 1988); vertical incident global solar radiation (Foster and Oreszczyn 2001); and, duration of occupation/absence (Pigg, Eilers et al 1996;Mahdavi and Proglhof 2009). In the present study, it was decided that all parameters would be monitored so as to later assess to what extent the observed behaviour agrees with the behaviour suggested by each model.…”
Section: Methodsmentioning
confidence: 99%
“…The occupants' control patterns observed during the monitoring campaign were compared to four of the most cited behavioral models indicated in the literature: two related to the control of the electric lighting -Switch On probability (Hunt 1979) and Switch Off probability (Pigg, Eilers et al 1996) -and two related to the control of the shading systemsopening/closing shading algorithm (Haldi and Robinson 2009) and closing probability (Inkarojrit 2008). The predicted probability for an action (computed based on environmental conditions) was compared against the frequency with which such adjustment was observed during monitoring.…”
Section: 11mentioning
confidence: 99%
“…The way it is expressed in the model, blind closing behaviour is driven by indoor and outdoor air temperature. Inkarojrit's (Inkarojrit 2008) results showed that the frequency of window blind closing events increased as the luminance and vertical solar radiation levels (direct normal radiation) increased. He built multiple models based on longitudinal logistic regression using one to four input variables.…”
Section: Resultsmentioning
confidence: 97%
“…be able to represent more OB models in the schema, more Drivers and Systems should be added, and the definition of Needs should be broader to accept more types of models. Some researchers used mathematical formulas that have not yet been implemented in obXML, such as the logit function with four independent variables used by the M1 model of Inkarojrit (Inkarojrit 2008). Therefore, an equation editor should be developed to provide freedom for users.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research investigate the operation of shading devices based on parameters such as vertical illuminance, irradiance, and window luminance levels (Reinhart and Voss 2003;Inkarojrit 2008;Lee et al 2005). Several metrics have been introduced over the past decade to evaluate glare from a given viewpoint.…”
Section: Glare Evaluationmentioning
confidence: 99%